Surface Ocean Dispersion Observations From the Ship-Tethered Aerostat Remote Sensing System - Carlson, Daniel F.; Özgökmen, Tamay; Novelli, Guillaume; Guigand, Cedric; Chang, Henry; Fox-Kemper, Baylor; Mensa, Jean; Mehta, Sanchit; Fredj, Erick; Huntley, Helga; Kirwan, A. D.; Berta, Maristella; et al. (Frontiers in Marine Science, 2018)
Oil slicks and sheens reside at the air-sea interface, a region of the ocean that is notoriously difficult to measure and, therefore, little is known about the velocity field at the sea surface. The Ship-Tethered Aerostat Remote Sensing System (STARSS) was developed to measure Lagrangian velocities at the air-sea interface by tracking the transport and dispersion of hundreds of drift cards in the field of view of a high-resolution aerial imaging system. The camera had a field of view of approximately 300 m X 200 m and images were obtained every 15 seconds over periods of up to 3 hours during a series of experiments in the northern Gulf of Mexico in January-February 2016. STARSS was equipped with a GPS and inertial navigation system (INS) that was used to directly georectify the aerial images. A relative rectification technique was developed that translates and rotates the drift cards to minimize the total movement of all drift cards from one frame to the next. Rectified drift card positions were used to quantify scale-dependent dispersion by computing relative dispersion, relative diffusivity, and velocity structure functions. STARSS was part of a nested observational framework, which included deployments of large numbers of GPS-tracked surface drifters from two ships, in situ ocean measurements, and X-band radar observations of surface currents. STARSS operations were supported by weather forecasts from a high-resolution coupled atmosphere-wave-ocean model. Here we describe the STARSS system and image analysis techniques, and present results from an experiment that was conducted on a density front. To the best of our knowledge, these observations are the first of their kind and STARSS-like observations can be adopted into existing and planned oceanographic campaigns to produce a step-change in our understanding of small-scale and high-frequency variability at the air-sea interface.